2018
DOI: 10.3390/coatings8110406
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Screen-Printing Performance of Model Silver Pastes for Metallization of Si-Solar Cells

Abstract: Further strong growth of solar energy conversion based on PV (photovoltaic) technology requires constant improvement to increase solar cell efficiency. The challenge in front-side metallization of Si-solar cells is to print uniform fine lines with a high aspect ratio to achieve higher efficiencies simultaneously with a reduced consumption of raw materials. An in-depth understanding of the relationship between paste composition, rheology and screen-printed line morphology is essential. Three model pastes with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Additionally, when a sufficient printability of front-side Ag paste at high flooding and printing speeds is desired, a low viscosity in the high shear regime seems to be necessary. [7][8][9][10][11][12] The printability in terms of sufficient paste transfer usually comes at the cost of inducing high shearing forces into the paste sample, resulting in significant spreading and the loss of high aspect ratios. Xu et al 13 and Tepner et al 1 showed in separate studies that an improved slip behavior of the paste during flooding could help to optimize this trade-off further because slip between the paste and emulsion surface allows for relative movement without the induction of unnecessary shearing forces.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when a sufficient printability of front-side Ag paste at high flooding and printing speeds is desired, a low viscosity in the high shear regime seems to be necessary. [7][8][9][10][11][12] The printability in terms of sufficient paste transfer usually comes at the cost of inducing high shearing forces into the paste sample, resulting in significant spreading and the loss of high aspect ratios. Xu et al 13 and Tepner et al 1 showed in separate studies that an improved slip behavior of the paste during flooding could help to optimize this trade-off further because slip between the paste and emulsion surface allows for relative movement without the induction of unnecessary shearing forces.…”
Section: Introductionmentioning
confidence: 99%
“…These achievements of screen printing have their origin in the continuous efforts of the industry around metallization to improve their technology and products and the scientific community providing an in‐depth insight into the underlying physics around that topic. Over the years, the latter provided various research studies, focusing on understanding the impact of paste rheology, [ 6–10 ] optimizing the electrical performance of Ag‐contacts, [ 11–14 ] and the impact of screen design on printing results. [ 6,15–19 ] Commonly available Ag‐pastes for front‐side PERC are highly filled suspensions containing up to 95 wt% spherical Ag‐particles with diameters below 5 µm.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22,28 ] and Yüce et al. [ 7,10 ] showed that this ability to maintain the finger geometry is closely related to the static yield stress. Below that stress level, the paste shows a more linear‐elastic response to applied stress as known from Hooke's law.…”
Section: Introductionmentioning
confidence: 99%
“…22 Upon the addition of a very small volume percent of this immiscible liquid, a dramatic change in rheological properties is observed. 23 The obtained capillary suspension exhibits an increase in the yield stress by several orders of magnitude, while showing shear-thinning behavior averting the need for potentially stress-inducing CMC, making these suspensions ideally suited for various printing applications 24,25,26 or ceramic bodies. 27 This change in properties is caused by the sample spanning particle network induced by capillary bridges of the secondary liquid.…”
Section: Introductionmentioning
confidence: 99%